2021
DOI: 10.1016/j.artd.2020.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Synergistic Effect of Topical Plus Intravenous Tranexamic Acid Versus Intravenous Administration Alone on Blood Loss and Transfusions in Primary Total Hip and Knee Arthroplasties?

Abstract: Background: The optimal route and dosing regimen of tranexamic acid (TXA) in primary total hip arthroplasty (THA) and total knee arthroplasty (TKA) remain unclear. As such, we sought to analyze if there was a synergistic effect of intravenous (IV) and topical TXA on blood loss and transfusions. Methods: We retrospectively analyzed 6720 primary TKAs and 6559 THAs performed from February 1, 2016 to December 31, 2019 at a single institution in patients who received a double IV dose (6159 TKAs and 6276 THAs) compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 13 For its part, topical administration provides maximum concentration of TXA in the surgical site associated with a minimal systemic effect, thus reducing possible systemic adverse effects. 14 , 15 Until now, the efficacy and safety of topical TXA compared to IV TXA for controlling blood loss and transfusions in TKA still remains controversial. Therefore, the new strategy of TXA administration, the combined regimen, has been explored.…”
Section: Discussionmentioning
confidence: 99%
“… 13 For its part, topical administration provides maximum concentration of TXA in the surgical site associated with a minimal systemic effect, thus reducing possible systemic adverse effects. 14 , 15 Until now, the efficacy and safety of topical TXA compared to IV TXA for controlling blood loss and transfusions in TKA still remains controversial. Therefore, the new strategy of TXA administration, the combined regimen, has been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, the controversy about whether TXA can reduce pain may be related to the following reasons: (1) for local use, TXA and normal saline are injected into the joint cavity by the drainage tube. Due to the abundant pain receptors around the hip joint are sensitive to pressure changes [ 27 ], a large amount of normal saline will lead to increased local pressure of the hip joint, triggering pain receptors and causing pain; (2) the local hemostatic effect was related to the dose of TXA [ 28 , 29 ], increased local bleeding leads to soft tissue swelling, which causes pain; (3) the use of more normal saline lead to a lower local concentration of TXA, which weakens the hemostatic effect according to the concentration-drug effect ratio, leads to increased local bleeding, increased tissue swelling and pain; (4) excessive less use of normal saline causes the TXA to be not evenly diffused into the whole joint cavity, that weakens the hemostatic effect and leads to more bleeding and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized comparison of 150 patients undergoing TKA with 1 g administered intra-articular, compared with 1 g IV and control, demonstrated intra-articular application reduced total blood loss more than IV administration ( P = .011) [ 76 ]. Finally, a study from 2016 to 2019 of more than 13,000 THA and TKA patients found that a double dose of IV TXA (1 g administered within 30 minutes of the skin incision and 1-g dose within 3 hours postoperatively) and a single 1 g IV dose within 30 minutes of the skin incision in combination with topical TXA (3 g diluted in 45 mL normal saline) resulted in equal rates of blood transfusion [ 12 ]. Regardless of route, evidence supports the effectiveness of TXA in reducing blood loss in TJA when administered in the perioperative period [ 21 , 56 ].…”
Section: Txa Route and Dosingmentioning
confidence: 99%